Integrating sustainability and technology: How green and digital marketing drive business performance through market orientation - Marlinah, Andi; Parawansa, Dian Anggraece Sigit; Hamid, Nurdjanah; Ismail, Muhammad (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the impact of green marketing and digital marketing on business performance, with a particular emphasis on the mediating role of market orientation. A quantitative research design was employed, using a structured questionnaire distributed to 138 electric vehicle users in Makassar, Indonesia. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to assess both direct and indirect relationships among the studied variables. The results demonstrate that digital marketing significantly influences business performance both directly and indirectly through market orientation. In contrast, green marketing does not have a direct effect but significantly enhances business performance indirectly via market orientation. The study concludes that market orientation is a crucial mediating factor in translating sustainable and digital marketing efforts into improved business outcomes. These findings suggest that firms should strengthen their market orientation to fully leverage green and digital marketing strategies. By doing so, businesses can more effectively meet consumer expectations, adapt to technological changes, and address environmental challenges, thereby achieving sustainable competitive advantage and enhanced performance.